Effect of tannic acid irrigation on microhardness of root canal dentin and bond strength of epoxy resin based sealer - Sevinc Askerbeyli Örs; Hacer Aksel; Selen Küçükkaya Eren; Dilara Zeybek (Selçuk University, 2019)
Background:To investigate the effects of final irrigation protocols with tannic acid (TA) on dentin microhardness and push-out bond strength of an epoxy resin based sealer to root canal dentin.Methods: The 50 root halves were embedded in an acrylic resin for the microhardness measurement. After the initial baseline microhardness measurement, the root halves were randomly divided into 5 groups according to the final irrigation protocol used (n=10): distilled water (control), 10% TA for 2 min, 10% TA for 5 min, 20% TA for 2 min, and 20% TA for 5 min. After surface treatment, dentin microhardness values were recorded at close proximity to the initial indentation areas. For push-out bond strength test the root canals of 75 single-rooted mandibular premolars were instrumented and the final irrigation protocols were applied as described above (n = 15). Following root canal obturation with single cone technique using matched-taper  gutta percha cones and an AH Plus- epoxy resin based root canal sealer, 1 mm-thick slices were obtained from the middle third of the root canals. Push-out bond strength test was applied. The data were analyzed using One way ANOVA and Tukey HSD tests (p=0.05).Results:In TA-treated groups, there was a significant increase in the microhardness values compared with the control group (p<0.05). Regarding the push-out bond strength test, there was no significant difference between the bond strength values of 10% TA for 2 min and the control group (p>0.05). The remaining groups presented higher bond strength values than the control group (p<0.05).Conclusions: TA increased dentin microhardness and the bond strength of the epoxy resin based sealer to root canal dentin. The effect on the bond strength was time and concentration dependent. Keywords: bond strength, dentin, microhardness, epoxy resin based sealer, tannic acid